2017
DOI: 10.1021/jacs.7b07311
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Nitrogenase H2 Formation by Metal-Hydride Protonation Probed by Mediated Electrocatalysis and H/D Isotope Effects

Abstract: Nitrogenase catalyzes the reduction of dinitrogen (N2) to two ammonia (NH3) at its active site FeMo-cofactor through a mechanism involving reductive elimination of two [Fe-H-Fe] bridging hydrides to make H2. A competing reaction is the protonation of the hydride [Fe-H-Fe] to make H2. The overall nitrogenase rate-limiting step is associated with ATP-driven electron delivery from Fe protein, precluding isotope effect measurements on substrate reduction steps. Here, we use mediated bioelectrocatalysis to drive el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 24 publications
2
55
0
Order By: Relevance
“…7; (74)). It is also possible that proton tunneling, which is generally thought to have a very large kinetic isotope effect (but also see 73,74) and has been proposed to occur in nitrogenase (82), could be contributing to the observed KIE, though we note that the temperature effect observed here is opposite of the predicted effect for tunneling (83,84).…”
Section: Mechanistic Implications For Nitrogenasementioning
confidence: 46%
See 1 more Smart Citation
“…7; (74)). It is also possible that proton tunneling, which is generally thought to have a very large kinetic isotope effect (but also see 73,74) and has been proposed to occur in nitrogenase (82), could be contributing to the observed KIE, though we note that the temperature effect observed here is opposite of the predicted effect for tunneling (83,84).…”
Section: Mechanistic Implications For Nitrogenasementioning
confidence: 46%
“…αH2O/H2 of Mo-nitrogenase(74). For example, it could be that the V-and Fe-only nitrogenases are less selective for1 H compared to the Mo-nitrogenase.…”
mentioning
confidence: 99%
“…There are few reports detailing the kinetic parameters for hydride transfer from a transition metal center to CO 2 . Independent of this dearth of detailed kinetic studies, two mechanistic pathways are proposed: normal insertion wherein an H – attacks the π* orbital of CO 2 , and abnormal insertion in which a metallocarboxylate is generated , . The latter pathway is typically invoked for CO 2 reduction to CO and H 2 O, whereas the former leads to formate.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al also adopted this approach to demonstrate that the MoFe and FeFe proteins could reduce CO 2 to HCOO − with respective FEs of 9% and 32%. Khadka et al also demonstrated that this approach could be employed to investigate the rate-limiting step of the MoFe when catalyzing H + reduction [170]. In this study, the cobaltocene concentration was titrated such that electron transfer to the MoFe protein was not limiting, and bioelectrocatalytic H + reduction to H 2 was evaluated as a function of catalytic current.…”
Section: Electrochemical Methods For Electron Transfermentioning
confidence: 98%